(untitled) (Philological Studies, 2019)
In this paper dedicated to the poetry of Slave Gjorgjo Dimovski (1959), more precisely to his poetry book "Reports of the Lynx" (2016), I will try to argue that Dimovski’s book is more than a successful poetic writing which in itself contains the idea of the sublimity of nature, but at the same time, the idea of discomfort of the society (that is, the culture) that threatens it and even leads it to extinction. In addition to these epistemological and environmentalist approaches, the aesthetic approach that will point to the undeniable literary value of this poetic manuscript, which is one of the most successful achievement within the contemporary Macedonian poetry, will not remain aside.